2019
DOI: 10.1016/j.ajog.2019.01.228
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of miR-324/KISS1/kisspeptin in early ectopic pregnancy: mechanistic findings with clinical and diagnostic implications

Abstract: Background: Ectopic pregnancy (EP) is a life-threatening condition, for which novel screening tools enabling early accurate diagnosis would improve clinical outcomes. Kisspeptins, encoded by KISS1, play an essential role in human reproduction, at least partially by regulating placental function and possibly embryo implantation. Kisspeptin levels are massively elevated in normal pregnancy and reportedly altered in various gestational pathologies. Yet, the pathophysiological role of KISS1/kisspeptin in EP has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Much has been published about the peripheral regulatory roles of kisspeptin in female fertility. Kisspeptin and its receptor KISS1R have important roles in regulating follicle development, oocyte maturation, ovulation, ovarian steroidogenesis, implantation, pregnancy, and placentation [36,[54][55][56]. However, less is known about the peripheral reproductive roles of the tachykinin family and the roles of kisspeptins and tachykinins in male reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much has been published about the peripheral regulatory roles of kisspeptin in female fertility. Kisspeptin and its receptor KISS1R have important roles in regulating follicle development, oocyte maturation, ovulation, ovarian steroidogenesis, implantation, pregnancy, and placentation [36,[54][55][56]. However, less is known about the peripheral reproductive roles of the tachykinin family and the roles of kisspeptins and tachykinins in male reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In female reproductive tissues, kisspeptins are involved in the regulation of a wide variety of processes including follicular development, oocyte maturation, ovulation, ovarian steroidogenesis, embryo implantation, and placentation [53][54][55][56]. In the case of males, kisspeptins are suggested to play important regulatory roles in spermatogenesis, testicular steroidogenesis, and spermatozoa function, as is discussed in the following sections [43,54].…”
Section: Kisspeptinsmentioning
confidence: 99%
“…A study by de Roux et al demonstrated that humans with a defect in the GPR54 gene exhibit isolated hypogonadotrophic hypogonadism, suggesting that kisspeptin is an important regulator of gonadal axis development [59]. This finding was then reproduced by an independent study by Seminara et al, who evaluated a large family with idiopathic hypogonadotrophic hypogonadism and generated GPR54 knockout mice, which failed to undergo adult sexual development and had low serum gonadotropin levels [47]. In contrast, exogenous kisspeptin administration in prepubertal rodents and primates has been shown to induce precocious puberty [60].…”
Section: Kisspeptin In Pubertymentioning
confidence: 97%
“…Kisspeptin has been shown to be massively downregulated in the case of ectopic pregnancy [47]. Ectopic pregnancy occurs when a fertilized ovum implants and develops outside the uterine cavity.…”
Section: Kisspeptin In Pregnancymentioning
confidence: 99%
“…23,24) miR-324 is located on 17p13.1 and has been confirmed to take effects on various physiological function in many diseases, such as cancers, [25][26][27][28] Parkinson's disease, 29) polycystic ovarian syndrome, 30) and early ectopic pregnancy. 31) In addition, miR-324 has been proven to participate in the protection of urocortin against myocardial ischemia-reperfusion injury. 32) However, details on the regulatory and potential functional mechanisms of miR-324 in myocardial ischemia have never been reported.…”
mentioning
confidence: 99%